Monitoramento do nível de combustível do tanque do grupo gerador do datacenter da UFT utilizando microcontrolador ESP8266 - Silva, Wecleson Brandão da (Universidade Federal do Tocantins, 2020)
The need for monitoring and control in industrial processes remotely and 1n real time has grown categorically in recent years, leading to the connectorization of various equipment to the worldwide computer network that provide the sensing and performance 1n the environment that are inserted. Thus, m environments with high demand for the availability of the services provided, such as data centers with their Information and Communication Technology (ICT) services, It 1s no different, it is necessary to control the environmental conditions to maintain the service. its proper functioning and reliability. In data centers, power supply failures are one of the situations that should be avoided as much as possible so as not to affect the services provided. Therefore, own power supply systems are built in case of interruption of electricity supply by the electric utility. In this context, the real-time monitoring of the fuel level of the diesel tank that supplies the electricity generator group that serves the data center of the Federal University of Tocantins 1s proposed. For this, a solution was developed using the ESP8266 microcontroller connected to the internet, real time database and Web application for proper fuel level visualization.